F2 Examination Hall Reservation Management System - Leng, Hooi Qi; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2024)
The University Tun Hussein Onn Malaysia (UTHM) faces challenges with manual hall booking management, which causes issues with accessibility, transparency and efficiency. This study introduces the F2 Examination Hall Reservation Management System, which aims to improve operational efficiency by automating the reservation process for UTHM staff and students through the Academic Management Office (PPA). The system is constructed using the Waterfall model as its primary methodology, integrating HTML, CSS, JavaScript, PHP and MySQL. The developer used tools like Visual Studio Code for coding and XAMPP for local hosting and testing to ensure efficient processes. Findings show that the reservation procedures have significantly improved. The study supports the system's wider adoption and potential improvements by highlighting its critical role in displacing manual techniques.